Effects of mitotane on testicular adrenal rest tumors in congenital adrenal hyperplasia due to 21-hydroxylase deficiency: a retrospective series of five patients. Issue 3 (March 2021) - Bachelot, Anne; Lapoirie, Marion; Dulon, Jérôme; Leban, Monique; Renard Penna, Raphaële; Touraine, Philippe
Abstract : We conducted a retrospective study on the long-term effect of mitotane treatment on testicular adrenal rest tumors (TARTs) in five adult patients with classic 21-hydroxylase deficiency. After 60 months of mitotane treatment, a decrease in adrenal steroids was observed in four patients. Testicular ultrasonography showed complete disappearance of TART in two patients, stabilization in two patients and a halving of TART volume in the remaining patient. Sperm count improved notably in two patients who had normal baseline inhibin B levels and small inclusions, thus enabling cryopreservation of the subjects' semen. Four years of follow-up of these two patients after the withdrawal of mitotane showed no recurrence of TART and persistent normal testicular function. In conclusion, mitotane could be used as a last resort in CAH patients in the cases of azoospermia associated with TARTs but normal inhibin B levels, as it can improve long-term endocrine and exocrine testicular function.